Response of the equatorial and low-latitude ionosphere to an intense X-class solar flare (X7/2B) as observed on 09 August 2011 - Sripathi, S.; Balachandran, N.; Veenadhari, B.; Singh, Rajesh; Emperumal, K. (My University, 2013)
In this paper, we present response of equatorial and low-latitude ionosphere to an intense solar flare of class X7/2B that peaked at 08:05 UT on 09 August 2011 in the solar cycle 24. Global positioning system total electron content (TEC) observations in the sunlit hemisphere show enhancement of ~3 TEC units, while geomagnetic H component observations indicate sudden decrease and increase in their strength at equatorial and low-latitude stations, respectively, at several stations in the sunlit hemisphere. In addition, equatorial electrojet strength over Indian region reveals commencement of counter electrojet. Simultaneous Canadian Advanced Digital Ionosonde observations at Tirunelveli, an equatorial station in India, show the disappearance of ionogram echoes during the flare event indicating absorption of radio signals in the D region. Strong equatorial blanketing type Es layer was observed in the ionogram records at Tirunelveli prior to the occurrence of the solar flare that continued for several hours though it became weak/absent during the flare event. Ionogram records on the control day show regular F layer movement without any blanketing type Es layer. Very low frequency (VLF) observations at Allahabad, an Indian low-latitude station, show enhanced VLF amplitude signal during the same time revealing the sudden enhancement of D region ionization. Using the observations presented here, an attempt has been made to study the impact of the solar flares on the electrodynamics of the equatorial and low-latitude ionosphere.
Keywords: Low-latitude ionosphere; X-class solar flare; Total electron content; Equatorial electrojet